Exploring the relationship between established HIV risk factors and depressive symptoms amongst young women without HIV in two sites in South Africa - Zanenhlanhla Gumbi; Celia Mehou-Loko; Lindi Masson; Makhosazana Mdladla; Nokuthula Maphumulo; Jo-Ann Passmore; Sanele Mbeje; Linda Gail Bekker; Disebo Potloane; Heather Jaspan; Nina Radzey; Andrea Abrahams; et al. (PLoS ONE, 2025)
Purpose Adolescent girls are at high risk for depression and human immunodeficiency virus (HIV) acquisition. Poor mental health can increase vulnerability to risky sexual behaviours. Therefore, this study aims to determine the prevalence of depressive symptomology and explore the convergence of HIV risk factors with depressive symptoms amongst cis-gender adolescent girls and young women (AGYW) in rural KwaZulu-Natal (KZN) and peri-urban Western Cape (WC) communities in South Africa. Methods Cross-sectional survey data from two sites in South Africa was used - the rural Vulindlela community in KZN and the peri-urban Philippi East community in the WC. Study inclusion criteria included being sexually active with at least one male partner, and not planning to relocate in the next 12 months. The PHQ-9 scale was used to determine depressive symptomology, a socio-behavioural questionnaire was used to determine sexual behaviours, odds ratios and confidence intervals derived from logistic regression models were used to explore the associations between depressive symptomology and socio-behavioural factors associated with HIV acquisition. Results The cohort consisted of 274 adolescent girls, 38.6% from the WC site and 61.4% from the KZN site. Overall, 15.7% (43/274) of AGYW reported depressive symptoms. Participants from the peri-urban WC site were more likely to experience depressive symptoms (OR 8.34; 95% CI 3.80–18.30) compared to those living in the rural KZN site. Depressive symptoms were less likely to occur in adolescent girls between the ages of 14 to 17 as compared to those between the ages of 18 and 19 (OR 0.44; 95% CI 0.22–0.90). Socio-behavioural HIV risk factors associated with depressive symptoms include: age disparate relationships (OR 2.98; 95% CI 1.52–5.84), high (four or more) numbers of lifetime partners (OR 8.15; 95% CI 3.60–18.45) and engaging in sex under the influence of alcohol (OR 2.58; 95% CI 1.32–5.04). Multivariate analysis showed that participants from the WC site (AOR 5.25; 95% CI 1.95–14.17) had higher odds of experiencing depressive symptoms while participants with four or more lifetime partners (AOR 3.46; 95% CI 1.24–9.60) were at higher odds of experiencing depressive symptoms. Conclusion In this cross-sectional study, depressive symptomology is associated with certain HIV risk behaviours. Longitudinal studies are required to test the causal relationship between depression and HIV acquisition and to better understand the geospatial differences observed.